2023
DOI: 10.1111/spsr.12554
|View full text |Cite
|
Sign up to set email alerts
|

Do Citizens Judge Health Experts Through a Partisan Lens? Evidence from a Factorial Survey Experiment

Abstract: Scholars have claimed that right‐wing citizens are more skeptical about experts than left‐wing citizens. This article, however, argues that depending on their party affiliation, citizens prefer certain kinds of expertise over others. I confronted Swiss adults (N = 2,465) with individual risk advice on either flu vaccination or colorectal cancer screening. The quote varied regarding the expert providing the advice (e.g., academic, administration, or corporation) and the degree of policy advocacy. The citizens t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated the importance of partisanship in voting choice (Achen and Bartels, 2016;Campbell et al, 1960). In this regard, a recent study on the Swiss case highlights that partisanship affects the way Swiss citizens perceive experts (Hanimann, 2023). At the same time, over the last decades, citizens have also become increasingly critical of parties (Dalton, 2000;Ignazi, 2014, Van der Meer andOuattara, 2019), loosening traditional partisan ties (Önnudóttir and Harðarson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated the importance of partisanship in voting choice (Achen and Bartels, 2016;Campbell et al, 1960). In this regard, a recent study on the Swiss case highlights that partisanship affects the way Swiss citizens perceive experts (Hanimann, 2023). At the same time, over the last decades, citizens have also become increasingly critical of parties (Dalton, 2000;Ignazi, 2014, Van der Meer andOuattara, 2019), loosening traditional partisan ties (Önnudóttir and Harðarson, 2020).…”
Section: Introductionmentioning
confidence: 99%